ASSOCIATION OF SERUM CA-125 LEVELS WITH NON-HODGKIN’S LYMPHOMA - Samad, Fauzia Abdus; Syed, Abdus Samad (Pakistan Journal of Physiology, 2017)
Background: Non-Hodgkin’s lymphoma (NHL) is a common malignancy presenting to oncology out-patient departments. Several prognostic markers including lactate dehydrogenase (LDH), BCL-2 and beta-2 micro-globulin have been studied and have been found to be of significance. Serum CA-125 has been studied in the past and feeble but unclear association was found. The present study aims at finding an association between serum CA-125 levels and NHL. Methods: One hundred patients (90 males, 10 females) with histological diagnosis of NHL diffuse large B-cell type were enrolled in the study through convenience sampling method. After documenting the demographics (age, gender and performance status), staging investigations including bone marrow aspiration/trephine, CT scans, baseline haematology and biochemistry. Serum LDH and serum CA-125 levels were measured at diagnosis and completion of treatment. Results: Fifty-eight patients had normal serum CA-125 levels while 42 patients had raised levels. Patients with high CA-125 levels at baseline had higher international prognostic scores. These patients had poorer response to treatment. Raised CA-125 levels were found more frequently among patients who had ascites or pleural effusions due to lymphoma. Conclusion: Serum CA-125 level measurement before during and after treatment correlates with response to treatment and increasing levels following treatment completion can predict disease relapse ahead of time. Pak J Physiol 2017;13(1):54–6